Union Territory of Dadra and Nagar Haveli, Annual Plan 1970-71 - Planning Commission (Planning Commission, 1971)
The Union Territory of Dadra and Nagar Haveli 19 a small Union Territory and hence is administered as a single administrative Unit. All the officers are functioning simultaneously from Taluka to state level. The strategy of development for the TV to plan period can be summarized thus Increase in agriculture production by at least 5$ over the next decade year improvement in the economic and social Hans of the people by way of education, increase in industrial and exploitation of natural resources, The bulk of Population comprise of Advises and hence some inducement by way of relieving the financial burden is necessary. One of the major schemes of the Administration is to settle the landless agricultural laborers and about 1000 landless agricultures families would have been settled by the end of the IV Five Year Plan period.
Union Territory of Dadra and Nagar Haveli
Union Territory of Dadra and Nagar Haveli
Keywords: Union Territory of Dadra and Nagar Haveli; Annual Plan 1970-71; Landless Agricultural Laborers; Socio Economic Development; small territory; Agriculture; Economic Development; Accordingly the provisions; irrigation; Damanganga project; Manures and Fertilizers; Green Manures and Seeds; Plant Protection Schemes; Supply of Improved Seeds; Administrative policy and Institution framework